Comparative Study of Static and Dynamic Hand Grip Endurance with Correlation of Deep Breathing among Pregnant Women; A Cross-sectional Study - Saman Babar, Muhammad Haris, Mirza Zeeshan Sikandar, Umair Abu Bakar Siddiq, Saqib Javaid Ahmad, Farah Shaheen (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Physiology of the mother, changes constantly during pregnancy including reduced HGS that is require for carrying the child after delivery. Activities of daily living require manual gripping tasks that require dynamic and static contractions. Predictor of upper extremity function is Hand Grip Strength and handgrip endurance. Screening of hand grip strength during antenatal care is still uncommon. Objectives: To compare static and dynamic hand grip endurance in pregnant females and to find its correlation with deep breathing. Material and Methods: The study recruited 40 participants of primi-gravida of 1st and 2nd trimester, between ages 20 and 35 years from SHALAMAR GYNAE OPD. The participants assigned to the groups (Group 1: with DB, Group 2: without DB) based on their trimester and gravidity. Static and dynamic endurance assessed using hand held dynamometer. Results: Mean Age ± Standard deviation for deep and non-deep breathing groups was 22.85 ± 2.30 and 24.05 ± 0.514. Age had negative little or low correlation with all variables of deep and non-deep breathing groups. Peak hand grip strength was moderately correlated with hand grip endurance with deep and non-deep breathing group (r = -0.628, r = -0.566 respectively). Static hand grip endurance was weakly correlated with peak hand grip strength in deep breathing group (r = -0.239) whereas static hand grip endurance had little, if any correlation with peak hand grip strength in deep breathing group (r = -0.165). Clinical implication: Management of hand grip strength and endurance improves general well being of pregnancy. By employing deep breathing exercises hand grip strength can be improved. Conclusion: Peak hand grip strength and endurance improved markedly in 2nd trimester with deep breathing. Deep breathing can improve peak hand grip endurance and peak hand grip strength in pregnancy with increasing trimester. Whereas static and dynamic hand grip endurance has insignificant effect in different trimester. Keywords: Pregnancy, deep breathing, trimester, endurance, peak grip endurance